2020
DOI: 10.1002/jcla.23520
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microRNA processing machinery gene (DROSHA, DICER1, RAN, and XPO5) variants association with end‐stage renal disease

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
(108 reference statements)
0
6
0
Order By: Relevance
“…Although we did not find a relationship between hypospadias and consanguinity ( p = .185), the marriage between close relatives has been associated with an increased risk of familial hypospadias. Several studies have reported cases of hypospadias in consanguineous families, suggesting a potential genetic influence on the condition (Frydman et al, 1985;Mohamed et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we did not find a relationship between hypospadias and consanguinity ( p = .185), the marriage between close relatives has been associated with an increased risk of familial hypospadias. Several studies have reported cases of hypospadias in consanguineous families, suggesting a potential genetic influence on the condition (Frydman et al, 1985;Mohamed et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This variant has shown a negative association with the development of multiple sclerosis (Basak et al, 2022), recurrent implantation failure (Lee et al, 2020), venous thromboembolism (Ko et al, 2019), pregnancy‐induced hypertension (Huang et al, 2019), and type 2 diabetes mellitus and its vascular complications (Wen et al, 2019). Conversely, this genetic variant has shown associations with endometriosis (Cardoso et al, 2021), recurrent spontaneous abortion (Ghasemi et al, 2020), dermatomyositis (Peng et al, 2023), end‐stage renal disease (Fawzy et al, 2020), papillary thyroid carcinoma (Mohammadpour‐Gharehbagh et al, 2020), colorectal cancer risk (Kim et al, 2019), pseudoexfoliation glaucoma (Kondkar et al, 2022), primary open‐angle and angle‐closure glaucoma (Kondkar et al, 2023), and pregnancy‐induced hypertension (Khabour et al, 2023) (as outlined in Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, miRNAs regulate gene expression by attaching to the 3′ untranslated region (3′ UTR) of target mRNAs, but any alteration in expression of synthesized miRNA could affect hundreds of genes [ 43 ]. miRNA biogenesis genes and their variants are involved in the pathogenesis of several diseases, including HCC [ 12 , 44 , 45 ]. To the best of our knowledge, this work is the first to study the association of the XPO5*rs34324334 and RAN*rs14035 variants with increased risk of HCC among Egyptian subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the high quality of the genotyping assays (ie, the genotyping call rate = 100%, with unambiguous allelic discrimination plots) suggested a violation of HWE assumptions in the study groups rather than technical genotyping errors as proposed by Esser et al 23 and experienced in our previous publication. 18 The CTLA4 rs231775 variant has been reported to be associated with various autoimmune diseases such as Graves' disease in adults 24 and autoimmune hypothyroidism in children of the Han Chinese population, 25 multiple sclerosis, 26 vitiligo, 7 vasculitis, 27 systemic lupus erythematosus, [28][29][30] rheumatoid arthritis, 31,32 latent autoimmune diabetes in adults, 33 primary biliary cirrhosis, 34 primary biliary cholangitis, 35 and Pemphigus Vulgaris. 36,37 Additionally, a more recent meta-analysis by Wang and colleagues indicated a significant association of CTLA4 rs231775 with autoimmune diseases' susceptibility under different genetic models, highlighting its potential implication as a diagnostic genetic biomarker in both Asian and Caucasian populations.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 PCR reactions were run in duplicates in a 25-µl final volume contain- previously. 18 Hardy-Weinberg equilibrium (HWE) was calculated by SNPstats (https://www.snpst ats.net/). 19 Genotype-specific adjusted odds ratios (ORs), and the 95% confidence intervals (CIs) were calculated by logistic regression analyses, and all the association analyses under the five genetic associations models were tested.…”
Section: Ctla4 Rs231775 (C49a>g) Variant Analysismentioning
confidence: 99%